2016
DOI: 10.1186/s13550-016-0167-x
|View full text |Cite
|
Sign up to set email alerts
|

Radiolabeling polymeric micelles for in vivo evaluation: a novel, fast, and facile method

Abstract: BackgroundSingle photon emission computed tomography (SPECT) is an indispensable tool in the determination of the in vivo fate of polymeric micelles. However, for this purpose, the micelles need to be radiolabeled, and almost all radiolabeling procedures published to date involve the conjugation of a chelating agent to the constituting polymer, which could actually affect their biodistribution. In this paper, we report a new facile method for radiolabeling polystyrene-b-poly(ethylene oxide) diblock copolymer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 24 publications
0
26
1
Order By: Relevance
“…Other cell types such as mesenchymal stem cells 53, 54 and endometrial cells 55 have also been successfully radiolabelled using [ 111 In] Trop. More recently, [ 111 In]Trop was used to label polymeric micelles 56. The orientation of exosomal transmembrane proteins is the same as their parent cells 15 and therefore provides the opportunity for them to be radiolabelled using the same principle.…”
Section: Resultsmentioning
confidence: 99%
“…Other cell types such as mesenchymal stem cells 53, 54 and endometrial cells 55 have also been successfully radiolabelled using [ 111 In] Trop. More recently, [ 111 In]Trop was used to label polymeric micelles 56. The orientation of exosomal transmembrane proteins is the same as their parent cells 15 and therefore provides the opportunity for them to be radiolabelled using the same principle.…”
Section: Resultsmentioning
confidence: 99%
“…In a facile and robust method developed by Laan et al (2016), tropolone and 111 In were entrapped in the core of micelles, without the surface conjugation of the chelator that might lead to altered biological behavior and compromised stability. Ex vivo biodistribution studies in healthy mice demonstrated high liver and spleen accumulation and significant blood circulation even at 24h post-injection [69].…”
Section: Indium-111mentioning
confidence: 99%
“…Ex vivo biodistribution studies in healthy mice demonstrated high liver and spleen accumulation and significant blood circulation even at 24h post-injection [69]. Micelles crosslinked with pluronic unimers and more specifically poly(ethylene oxide) and poly(propylene oxide) (PEO-PPO-PEO), and radiolabeled with 111 In via DTPA, were studied with respect to in vivo biodistribution using SPECT.…”
Section: Indium-111mentioning
confidence: 99%
“…The method used to encapsulate the radioisotope 111 In in the core of the micelles is based on the method developed by Laan et al 30 where the isotope is complexed with the lipophilic chelator tropolone.…”
Section: Radiolabeling and Purification Of Ps-peo Micellesmentioning
confidence: 99%